Clinical evaluation of SafeCEC® one-way valve in hemolysis during CPB: Pilot study - Coutinho Henrique Madureira da Rocha; Coutinho Joaquim Henrique de Souza Aguiar; Torres José Hamilton; Casanova Rafaela Mourão; Kikuta Gustavo; Reis Edison Emídio (The Journal of ExtraCorporeal Technology)
Introduction: In cardiopulmonary bypass (CPB), blood circulation is temporarily maintained by an artificial blood-pumping device during cardiac surgery. Worldwide, approximately half of the CPB procedures utilize either centrifugal or roller pumps (Wu P et al. Front Physiol 12, 699891). Centrifugal pumps, while non-occlusive, pose a risk of blood reflux if there is a system failure, which endangers patient safety (Souza MHL, Elias DO. Fundamentos da Circulação Extracorpórea 2006; 186–192). SafeCEC®, a one-way valve, offers a potential solution to this risk by preventing arterial line reflux. This pilot study aims to evaluate patient safety by analyzing hemolysis as an evaluation parameter. Plasma free hemoglobin is chosen to measure patient safety with the use of the product, ensuring it does not cause additional hemolysis during extracorporeal circulation. Materials and methods: After approval by the Ethics Committee, 31 patients undergoing CPB with a centrifugal pump were included in the study. The patients were randomly divided into two groups: group A, where SafeCEC® was incorporated into the arterial line, and group B, which used the conventional circuit. Hemolysis was assessed by analyzing plasma free hemoglobin in blood samples collected before CPB, after CPB, and 24 h after weaning from CPB. Results: This device has been shown to be effective in controlling blood reflux, eliminating the need for arterial line clamps. Analysis of plasma free hemoglobin levels revealed no significant differences between the groups with or without SafeCEC®. Conclusion: The SafeCEC® one-way valve effectively prevents reflux without contributing to blood damage, as indicated by the absence of significant hemolysis. This pilot study demonstrates that the SafeCEC® is both safe and effective for its intended use.